2009
DOI: 10.1143/jpsj.78.034402
|View full text |Cite
|
Sign up to set email alerts
|

Crack-Tip Stress Concentration and Structure Size in Nonlinear Structured Materials

Abstract: We revisit the standard elastic-plastic fracture theory developed by Hutchinson, Rice, and Rosengren (HRR) and reproduce, by a simple scaling argument, the stress singularity around the crack tip derived by HRR. From the singular behavior thus reconfirmed, we propose a general scaling relation which guarantees an effect similar to the tip-blunting effect: the maximum stress at the crack tip in a structured material can be reduced by increasing the structure size. This proposed relation is explicitly confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…This is a generalized version of a nonlinear Griffith's failure formula that was proposed theoretically in Ref. [49] and confirmed experimentally in Ref. [50].…”
Section: Details Of Derivationsupporting
confidence: 64%
See 1 more Smart Citation
“…This is a generalized version of a nonlinear Griffith's failure formula that was proposed theoretically in Ref. [49] and confirmed experimentally in Ref. [50].…”
Section: Details Of Derivationsupporting
confidence: 64%
“…In fact, this second principle is numerically confirmed in Refs. [49,54,55]. The authors considered a line crack of size a in a two dimensional nonlinear network system whose mesh size is d, and showed that, as expected, the maximum stress always appears at the crack tips.…”
Section: Details Of Derivationmentioning
confidence: 76%
“…where k and η are the spring constant and viscosity, respectively. Here, x i,j stands for the vertical position of the bead located originally at the lattice point (s = 1 and 3 correspond to shear and s = 2 and 4 correspond to stretch) [25]. 55 In order for a crack to propagate, every spring is broken when the force acting on it reaches the critical value f c .…”
Section: Simulation Modelmentioning
confidence: 99%
“…) with the natural length ℓ (s) of the springs with ℓ (1) = ℓ (3) = 0 and ℓ (2) = ℓ (4) = d (s = 1 and 3 correspond to shear and s = 2 and 4 correspond to stretch) [25].…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation